Implementing educational webquests as an effective tool for developing communicative competence among university students: a methodological aspect - Zhuparbek, D.; Nurkenova, S.S. (Karagandy University of the name of academician E.A. Buketov, 2025)
This article analyzes educational web quests as a teaching method for university students to develop communication skills. The main goal of the study is to assess the effectiveness of using web quests to develop students’ communication skills in various aspects: the grammatical structure of language, sociolinguistic contexts, and strategic competencies. The possibilities of integrating these methods into the educational process are also considered. The study design is based on the use of both qualitative research methods — such as experiments and questionnaires — and quantitative methods such as testing and content analysis. The study involved 120 students: 60 of them were assigned to the experimental group and the other 60 into the control group. The experiment lasted eight weeks; during this time, students from the experimental group completed various tasks based on educational web quests to apply theoretical knowledge in practice. The results of the study showed that the use of web quests improves students’ communication skills. On average, the score of the experimental group was 27% higher than the control group. Particular attention was paid to the development of discursive and strategic competencies, which contributed to the successful completion of tasks such as debating, writing essays, and creating multimedia projects by students. Web quests also stimulated student interest in learning, developing critical thinking, and interpersonal skills.
Университет студенттерінің коммуникативтік құзыреттілігін дамытуға арналған тиімді құрал ретінде білім беру веб-квестерін қолдану: әдістемелік аспект
Реализация образовательных веб-квестов как эффективного инструмента для развития коммуникативной компетенции студентов университетов: методологический аспект
Keywords: educational webquests; communicative competence; digital education; methodological aspect; innovative teaching methods; higher education; digital tools in education